The Solidity of Islamist Parties in Contemporary Southeast Asian Elections: A Comparative Analysis between the Malaysian Islamist Party (PAS) and the Prosperous Justice Party (PKS) - Ridho Al-Hamdi; Hanny Sri Handayani; Hamzah Fansuri; Nur Sofyan (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
This paper analyzes the solidity of two Islamist parties in contemporary Southeast Asian elections, the Prosperous Justice Party (PKS) in Indonesia and the Malaysian Islamist Party (PAS) in Malaysia. The aim is to discover the best model of party solidity, and, in turn, other Islamist parties can adopt the electoral performance of those two Islamist parties. Indeed, each party has its strengths and weaknesses. Therefore, it is fundamental to compare both of them. Methodologically, this study is qualitative research by employing appropriate literature studies, including news channels and social media platforms as the data collection. The findings demonstrated that PAS’ solidity was good in conflict resolution, as it could successfully govern the intra-party conflict between the conservative and the progressive factions. In the meantime, the PKS’ solidity tended to have a good performance in the party ideology. Overall, PAS had a better performance than PKS.